Hydrogel Mechanics Influence the Growth and Development of Embedded Brain Organoids - Cassel de Camps, Camille; Aslani, Saba; Stylianesis, Nicholas; Nami, Harris; Mohamed, Nguyen-Vi; Durcan, Thomas M; Moraes, Christopher (ACS applied bio materials, 2022)
Brain organoids are three-dimensional, tissue-engineered neural models derived from induced pluripotent stem cells that enable studies of neurodevelopmental and disease processes. Mechanical properties of the microenvironment are known to be critical parameters in tissue engineering, but the mechanical consequences of the encapsulating matrix on brain organoid growth and development remain undefined. Here, Matrigel was modified with an interpenetrating network (IPN) of alginate, to tune the mechanical properties of the encapsulating matrix. Brain organoids grown in IPNs were viable, with the characteristic formation of neuroepithelial buds. However, organoid growth was significantly restricted in the stiffest matrix tested. Moreover, stiffer matrixes skewed cell populations toward mature neuronal phenotypes, with fewer and smaller neural rosettes. These findings demonstrate that the mechanics of the culture environment are important parameters in brain organoid development and show that the self-organizing capacity and subsequent architecture of brain organoids can be modulated by forces arising from growth-induced compression of the surrounding matrix. This study therefore suggests that carefully designing the mechanical properties of organoid encapsulation materials is a potential strategy to direct organoid growth and maturation toward desired structures.